Magnitude of Multidrug Resistance among Bacterial Isolates from Surgical Site Infections in Two National Referral Hospitals in Asmara, Eritrea - Eyob Yohannes Garoy; Yacob Berhane Gebreab; Oliver Okoth Achila; Nobiel Tecklebrhan; Hermon Michael Tsegai; Alex Zecarias Hailu; Abrehet Marikos Buthuamlak; Tewelde Ghide Asfaga; Mohammed Elfatih Hamida (International Journal of Microbiology)
Background. The World Health Organization has emphasized the importance of understanding the epidemiology of MDR organisms from a local standpoint. Here, we report on a spectrum of bacteria associated with surgical site infections in two referral hospitals in Eritrea and the associated antibiotic susceptibility patterns. Methods. This survey was conducted between February and May 2017. A total of 83 patients receiving treatment for various surgical conditions were included. Swabs from infected surgical sites were collected using Levine technique and processed using standard microbiological procedures. In vitro antimicrobial susceptibility testing was performed on Mueller–Hinton Agar by the Kirby-Bauer disk diffusion method following Clinical and Laboratory Standards Institute guidelines. The data were analyzed using SPSS version 20. Results. A total of 116 isolates were recovered from 83 patients. In total, 67 (58%) and 49 (42%) of the isolates were Gram-positive and Gram-negative bacteria, respectively. The most common isolates included Citrobacter spp., Klebsiella spp., Escherichia coli, Proteus spp., Pseudomonas aeruginosa, Salmonella spp., Enterobacter spp., and Acinetobacter spp. In contrast, Staphylococcus aureus, CONS, and Streptococcus viridians were the predominant Gram-positive isolates. All the Staphylococcus aureus isolates were resistant to penicillin. MRSA phenotype was observed in 70% of the isolates. Vancomycin, clindamycin, and erythromycin resistance were observed in 60%, 25%, and 25% of the isolates, respectively. Furthermore, a high proportion (91%) of the Gram-negative bacteria were resistant to ampicillin and 100% of the Pseudomonas aeruginosa and Escherichia coli isolates were resistant to >5 of the tested antibiotics. The two Acinetobacter isolates were resistant to >7 antimicrobial agents. We also noted that 4 (60%) of the Klebsiella isolates were resistant to >5 antimicrobial agents. Possible pan-drug-resistant (PDR) strains were also isolated. Conclusion. Due to the high frequency of MDR isolates reported in this study, the development and implementation of suitable infection control policies and guidelines is imperative.